Forensic Pathology Reviews Vol 4 - Tsokos, Michael (Forensic Pathology Reviews, 2006)
Building on the excellent foundation laid in earlier volumes of the series, leading forensic pathologists from the United States and around the world again provide in Forensic Pathology Reviews, Volume 4 evidence-based accounts of special topics of current interest from various fields of forensic pathology and death-scene investigation. The authors offer cutting-edge insights into death from environmental conditions (lightning and elder abuse), homicide by sharp force, death from natural causes (asthma, Marfan syndrome, and peliosis of the liver and spleen), and pathology of human endothelium in septic organ failure. Additional chapters address special aspects of crime scene interpretation and behavioral analysis, neogenesis of ethanol and fusel oils in putrefying blood, agrochemical poisoning, imaging techniques in forensic pathology, and fixation techniques for organs and parenchymal structures. A comprehensive, up-to-date review of the international literature is given for each chapter. Evidence-based and state-of-the-art, Forensic Pathology Reviews, Volume 4 synthesizes the latest practical medical and scientific advances made in a variety of important subspecialties of forensic pathology, demonstrating how they are being applied to solve current problems of high interest to forensic pathologists.